Review of the current approaches to the assessment of the drug innovative potential worldwide - N. Z. Musina; V. K. Fedyaeva; V. V. Omel’yanovskii; G. R. Khachatryan; K. V. Gerasimova; V. A. Lemeshko; K. P. Konchits (Фармакоэкономика)
A set of criteria for assessing the innovative potential of drugs (therapeutic value) have been developed and are widely used elsewhere. These approaches allow the state (the payer) to assess the clinical significance of a new medical product and make an educated decision on the reimbursement, cost and priority at the stage of registration. In the Russian Federation though, such criteria and methods are not sufficiently developed. This review describes the principle approaches to assessing the drug innovative potential in countries outside Russia.